(untitled) (Международный научный журнал «Инженер», 2026)
The article is dedicated to the current problem of energy efficiency of buildings and structures, with a focus on the application of energy-efficient technologies in Uzbekistan. The experience of foreign countries in the construction of energy-efficient buildings, including the use of passive houses and modern thermal insulation materials, is considered. The article also analyzes Uzbekistan’s climatic features, which influence the choice of technologies and materials for construction. Special attention was paid to the issues of legislative and financial support, as well as the need to develop technologies adapted to local conditions. In conclusion, it is concluded that the transition to energy-efficient construction is important for the sustainable development of the country’s economy and ecology.